Aplikasi Panduan Budidaya Ayam Broiler Berbasis Android - Anshariah; Wahyuddin; Untung Suwardoyo (Sci-tech Journal, 2025)
This study develops an android-based broiler chicken cultivation guide application that provides information on how to cultivate broiler chickens. Although this cultivation effort can be done by anyone without special skills, it still requires guidance so that the business can run smoothly and profitably. Information on broiler chicken cultivation guides is widely available in various sources, such as books, online articles, and video tutorials. However, the information shared usually only discusses broiler chicken cultivation in general terms, which may not be in accordance with the needs and conditions of each farmer, making it difficult for farmers to find complete and efficient information. An Android-based broiler chicken cultivation guide application can be a solution to overcome these problems. Application development is carried out using Android Studio with the Java programming language. In this application, blackbox testing is also carried out to measure the functionality of the application and whitebox testing to measure the correctness of the program logic of the application. This application has various features such as getting to know broiler chickens, broiler chicken cultivation preparation, broiler chicken feed composition, initial growth phase maintenance, finisher period maintenance, broiler chicken diseases, harvest and post-harvest, prospects and how to calculate farmer profits and losses, as well as broiler chicken cultivation videos that can help farmers in carrying out broiler chicken cultivation efforts.